A responsabilidade social das empresas produtoras de petróleo: a regulação social como garantia de desenvolvimento - Paiva, Annuska Macedo Santos de França (2013)
This work aims to discuss the corporate social responsibility of oil producers in Brazil and to point which would be the adequate regulatory framework to ensure that those groups are fulfilling their constitutional social function, as this activity presents risks to Brazilian real development. The Social Oil Fund does not ensure the country is exempt from Dutch Disease and petropolitics. By linking the corporate activity to the social function, the Brazilian Constitution shows that the company not only has to be lucrative, but it also has social liabilities, respecting legal obligations and the community. This is the idea of corporate social responsibility, a management view based on instrumental motivations that brings benefits to the company, increasing its profit even indirectly. Based on a case study, only nine of the 40 oil producers in Brazil have social responsibility programs implanted in Brazil. The majority of those projects, however, consist of financial support to NGOs and are not related to social, economical and environmental consequences of the oil production. To ensure the social function, the State and stakeholders can sue the company for social damages, and class actions are suitable. Also, those groups can be contractually obliged to issue social impact reports and describe the actions taken by the company to diminish those violations. Last but not least, legal demands to ensure social function increase the minimum requirements for corporate social responsibility. This way, the regulation is soft, but with a hard core. The more social interests are exigible, the better are society s welfare and development.